Fault-related rocks : a photographic atlas - Snoke, Arthur W.; Tullis, Jan; Todd, Victoria R. (Victoria Roy) (Princeton legacy library, 1998)
This is a richly illustrated reference book that provides a unique, comprehensive, and up-to-date survey of the rocks and structures of fault and shear zones. These zones are fundamental geologic structures in the Earth's crust. Their rigorous analysis is crucial to understanding the kinematics and dynamics of the continental and oceanic crust, the nature of earthquakes, and the formation of gold and hydrocarbon deposits. To document the variety of fault-related rocks, the book presents more than six hundred photographs of structures ranging in scale from outcrop to submicroscopic. These are accompanied by detailed explanations, often including geologic maps and cross sections, contributed by over 125 geoscientists from around the world. The book opens with an extensive introduction by Arthur W. Snoke and Jan Tullis that is itself a major contribution to the field. Fault-related rocks and their origins have long been controversial and subject to inconsistent terminology. Snoke and Tullis address these problems by presenting the currently accepted ideas in the field, focusing on deformation mechanisms and conceptual models for fault and shear zones. They define common terminology and classifications and present a list of important questions for future research. In the main, photographic part of the book, the editors divide the contributions into three broad categories, covering brittle behavior, semi-brittle behavior, and ductile behavior. Under these headings, there are contributions on dozens of subtopics with photographs from localities around the world, including several "type" areas. The book is an unrivaled source of information about fault-related rocks and will be important reading for a broad range of earth scientists, including structural geologists, petrologists, geophysicists, and environmental specialists. Originally published in 1998. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905